2004
DOI: 10.1167/iovs.03-0796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TGF- 2 in Perfused Human Eyes

Abstract: TGF-beta2 reduces outflow facility when perfused into cultured human anterior segments. Furthermore, TGF-beta2 affects the extracellular matrix of the trabecular meshwork in a manner that is consistent with the observed reduction in outflow facility. Although the distribution of accumulated fibrillar material was different in these perfused eyes than that in POAG, the difference could be due to variation in biomechanical environment for TM cells in cultured anterior segments compared with the living eye. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
188
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(199 citation statements)
references
References 10 publications
5
188
0
1
Order By: Relevance
“…(Crawford et al 1998) Since TGFβ is thought to be of significance in affecting the normal and glaucomatous ECMs of the outflow pathway and has been shown to modify outflow facility, this may be of considerable importance. (Tripathi, RC et al 1994;Welge-Lussen et al 1999;Li et al 2000;Welge-Lussen et al 2000;Lutjen-Drecoll and Rohen 2001;Gottanka et al 2004) Immunostaining for thrombospondin 1 is observed throughout the TM, with the greatest density in the JCT region. (Flugel-Koch et al 2004) Tenascin C or hexabrachion is another matricellular protein expressed in the TM.…”
Section: Matricellular Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Crawford et al 1998) Since TGFβ is thought to be of significance in affecting the normal and glaucomatous ECMs of the outflow pathway and has been shown to modify outflow facility, this may be of considerable importance. (Tripathi, RC et al 1994;Welge-Lussen et al 1999;Li et al 2000;Welge-Lussen et al 2000;Lutjen-Drecoll and Rohen 2001;Gottanka et al 2004) Immunostaining for thrombospondin 1 is observed throughout the TM, with the greatest density in the JCT region. (Flugel-Koch et al 2004) Tenascin C or hexabrachion is another matricellular protein expressed in the TM.…”
Section: Matricellular Proteinsmentioning
confidence: 99%
“…(Parks and Mecham 1998) These stimuli include TNFα, IL-1α, TGFβ, dexamethasone, elevated pressure, and/or mechanical stretch. (Samples et al 1993;Clark et al 1995b;Alexander et al 1998;Bradley et al 1998;Bradley et al 2000;Bradley et al 2001;Gottanka et al 2004;Chen et al 2005;Clark et al 2005;Vittal et al 2005;Fleenor et al 2006;Kelley et al 2007) The process of ECM turnover is a concerted and highly coordinated program of degradation and biosynthetic replacement of specific ECM components. IOP homeostasis appears to be maintained, at lease in part by ECM turnover triggered in response to pressure changes or mechanical stretch or distortion, sensed by cells within the JCT.…”
Section: Ecm Turnover and Outflow Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with previous studies showing that TGF-b2 levels are higher in individuals with a glaucoma diagnosis. 9,10,12 These results, together with studies showing that TGF-b2 increases outflow resistance and IOP in ex vivo and in vivo glaucoma models, 15,16 support the idea that elevated levels of TGF-b2 contribute to the development of open-angle glaucoma.…”
mentioning
confidence: 73%
“…Eyes were stored in moistened chambers at 4°C until use. The perfusion protocol was similar to that described by Johnson and co-workers (Johnson and Tschumper 1987;Johnson and Tschumper 1989;Johnson 1996), with modifications described in detail previously by our group Gottanka et al 2004). Dulbecco's modified eagle medium (DMEM) was used as perfusate to which antibiotics (0.17 mg/ml Gentamycin, 0.25 μg/ml Amphotericin-B, 100 Units/ml Penicillin and 100 μg/ml Streptomycin; all from Sigma, St. Louis, USA), 1% fetal bovine serum (FBS, Sigma, St. Louis, USA) and 250 μg/ml bovine serum albumin (Sigma, St. Louis, USA) were added.…”
Section: Perfusion Studiesmentioning
confidence: 99%